KEWENANGAN DESA DALAM PENGELOLAAN PARIWISATA UNTUK MENDUKUNG PENINGKATAN PENDAPATAN DESA PASEBAN, KECAMATAN BAYAT, KABUPATEN KLATEN - Pangestu, Rizky Aji; Suranto, Suranto (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2018)
This study examines village authority in tourism management to support income improvement of Paseban Village, Bayat Sub-district, Klaten District. Besides, it is also to examine what is the obstacle of Paseban Village in managing tourism to support village income.The type of research used in this study is empirical legal research. Empirical or sociological law research is legal research by obtaining data through primary data or data obtained directly from the source. The research used descriptive qualitative approach. The author examines the authority of the village in the management of tourism to support income improvement Paseban Village, Bayat District, Klaten District and what obstacles that arise related to tourism management in Paseban Village and then find a solution to overcome these obstacles.Based on the results of the study and discussion, it will be concluded the authority of Paseban Village Government in managing tourism in order to improve the opinion of the village and what obstacles faced by Paseban Village Government in managing the tourism. The management of village original revenues is regulated in Articles 76 to 77 of Law No. 6 of 2014 on Villages, the lack of community involvement and the quality of the community in supporting the development of tourism in Paseban Village is a major problem in carrying out activities to increase the village’s original income.